Normative data of Fuld Object Memory Evaluation test for brazilian elderly population - Avila, Renata; Lopes, Marcos Antonio; Nakano, Eduardo Y.; Bottino, Cassio M.C (Arquivos de Neuro-Psiquiatria, 2016)
Objective This study aims to present normative data for Fuld Object Memory Evaluation test stratified by sex, gender, age, and education for the Brazilian elderly population.Method We evaluated 2.132 healthy elderly both genders, with a mean age of 70.30 years (± 7.28) from two community-based samples in Brazil drawn from different economic areas who were screened with cognitive and functional tests and the memory test. Statistical analyses were performed by independent t-test, one-way analysis of variance and multiple linear regression.Results Statistical analyses showed that memory scores tend to improve significantly with increasing years of education and decrease significantly as age increased.Conclusion We conclude that gender, education and age had effect on the Fuld Object Memory Evaluation performance in this Brazilian community-based sample.
Keywords: cognition; neuropsychological tests; dementia; long term memory; episodic memory; mild cognitive impairment